Understanding the Advantages and Disadvantages of Online Class during the COVID-19 Pandemic Lockdowns in Southern Philippines - Benito, Baby Sanor A.; Camral, King Alizon M. (Bumi Publikasi Nusantara, 2023)
This study aims to further understand the online approach to learning during the COVID-19 pandemic lockdowns in Southern Philippines. This study is based on Linda Harasim's theory of online collaborative learning, which emphasizes that rather than memorizing correct answers, students are encouraged to collaborate to solve problems through conversation. The teacher or instructor is a key player in this process. Collaborative learning is a method that involves students of various performance levels working together in small groups to accomplish a common goal. Students are responsible for each other's education in addition to their own. Face-to-face collaborative learning is being replaced by online collaborative learning.